2016
DOI: 10.1111/neup.12293
|View full text |Cite
|
Sign up to set email alerts
|

Gliosarcomas lack BRAFV600E mutation, but a subset exhibit β‐catenin nuclear localization

Abstract: Gliosarcoma (GS) is a rare subtype of glioblastoma (GBM) characterized by both glial and mesenchymal components. Unlike GBM, there are no specific prognostic markers, and optimized treatments for patients with GS do not exist. Recent reports describe BRAF mutation in malignant peripheral nerve sheath tumors, and aberrant Wnt signaling and CTNNB1 (β-catenin gene) mutations have been described in GBM. We sought to determine whether GS tumors harbor BRAF mutations or aberrant Wnt signaling, as indicated by nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…We also found the BRAFV600E mutation present in two patients (2/10, 20%), which is in contrast to the reported lack of BRAFV600E immunoreactivity in 48 gliosarcoma tumor sections [31], but in agreement with a recent finding [32]. Activating BRAF-V600E mutations are recurrently found in pediatric glial and glioneuronal brain tumors [12,33] and specific inhibitors are entering clinical trials.…”
Section: Discussionsupporting
confidence: 88%
“…We also found the BRAFV600E mutation present in two patients (2/10, 20%), which is in contrast to the reported lack of BRAFV600E immunoreactivity in 48 gliosarcoma tumor sections [31], but in agreement with a recent finding [32]. Activating BRAF-V600E mutations are recurrently found in pediatric glial and glioneuronal brain tumors [12,33] and specific inhibitors are entering clinical trials.…”
Section: Discussionsupporting
confidence: 88%
“…Several brain tumors have been described to frequently harbor the BRAF V600E mutation, including pleomorphic xanthoastrocytoma (PXA) (60%), anaplastic PXA (60%), ganglioglioma (GG) (20–60%), extracerebellar pilocytic astrocytoma (20%), and E‐GBM (50%) . However, gliosarcoma with BRAF V600E is extremely rare (1%) . In our case, both the sarcomatous and epithelioid components harbored BRAF V600E, leading us to consider a diagnosis of E‐GBM with a sarcomatous component.…”
Section: Discussionmentioning
confidence: 66%
“…[5][6][7] However, gliosarcoma with BRAF V600E is extremely rare (1%). [7][8][9] In our case, both the sarcomatous and epithelioid components harbored BRAF V600E, leading us to consider a diagnosis of E-GBM with a sarcomatous component.…”
Section: Discussionmentioning
confidence: 68%
“…Initial studies suggested that BRAF mutations are absent in gliosarcomas. However, BRAF V600E mutations were first described in a few case reports [84,85] and later in a study applying next generation sequencing in 10 gliosarcomas, which revealed BRAF V600E mutations in 2 cases [86]. We recently analyzed a cohort of 75 gliosarcomas and only one case harbored a V600E mutation, making it comparably rare as in GBM [67].…”
Section: Adult Brain Tumorsmentioning
confidence: 99%